Time junior middle school students invested to sports and their cognitive skill development: a time economics perspective - Hongmei Ma; Yan Liu (Scientific Reports)
Abstract Great importance is attached to physical exercise and students’ cognitive development, yet the precise mechanism linking the time duration of physical activities or sports with adolescents’ cognitive development remains inconclusive. Based on the two-wave panel data of China Education Panel Survey (CEPS), this paper empirically examines the impact of daily physical exercise duration on junior middle school students’ cognitive abilities, by using the two-way fixed-effect estimation. The findings reveal a nonlinear relationship, specifically an inverted “U”-shaped pattern, between daily time length of physical activities or sports and students’ cognitive performance. The cognitive benefits of time investment in physical activities or sports reach the peak at approximately 0.829 h (equivalent to 50 min) per day among the teenagers in China. Furthermore, the daily time allocated to physical activities or sports affects students’ cognitive performance differentially, students attending rural schools were rewarded more progressively, students of poorer physical fitness and those in good shape did not show discernible between-group differences. This study shades light on educational governance and time management, urging school administrators, parents and students to optimize the efficiency and utility of time resource invested in sports activities.